2007
DOI: 10.1093/cdj/bsn001
|View full text |Cite
|
Sign up to set email alerts
|

Teaching community development to social work students: a critical reflection

Abstract: Community development is generally considered to be a core component of social work practice and knowledge. Yet much professional social work education and discourse seems to relegate community development to the margins. This paper critically analyses the development of a community development subject within one particular Australian social work course. Particular attention is drawn to subject objectives, content, reading material, teaching methods and assessment. Some suggestions are made for new educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 22 publications
0
41
0
2
Order By: Relevance
“…Unlike the top-down model which is mainly defined by "outsiders," the bottom-up paradigm invokes the role of the local people in determining the type of intervention, priority setting, and implementation of the community programs. Also, this development paradigm concentrates on community empowerment (Flora & Flora, 1993;Mendes, 2009) and operates at the grassroots and not on the policy level (Brocklesby & Fisher, 2003).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Unlike the top-down model which is mainly defined by "outsiders," the bottom-up paradigm invokes the role of the local people in determining the type of intervention, priority setting, and implementation of the community programs. Also, this development paradigm concentrates on community empowerment (Flora & Flora, 1993;Mendes, 2009) and operates at the grassroots and not on the policy level (Brocklesby & Fisher, 2003).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In its more pragmatic institutional sense, it may be viewed as a means for mobilizing communities to join state or institutional initiatives that are aimed at alleviating poverty, solving social problems, strengthening families, fostering democracy, and achieving modernization and socio-economic development (Campfens 1997). According to Mendes (2008), community development is the "employment of community structures to address social needs and empower groups of people". It is a prime mover of people because it gets people to actively participate in issues that affect them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are arguments that locate community development as one method of social work intervention and others that argue that it is a separate discipline (Kenny, 2011). In a survey of Australian social work programmes, Mendes (2009) found that community development sat at the margins despite being described as a core subject. In New Zealand there are six Bachelor of Social Work programmes offered in four universities and one polytechnic offering community development as part of their courses, these vary in level from second to fouth year courses.…”
Section: The Role Of Community Development Within Social Workmentioning
confidence: 99%
“…Many argue that while there are inherent conflicts between community development and social work that separate them as disciplines, they are still linked by a shared interest in social justice (Mendes, 2009;Beddoe & Maidment, 2009). Such differences include a micro-focus versus a meso-or macro-focus, planned intervention versus collective action and the power relations that exist between the professional paid worker versus local (often volunteer) leadership.…”
Section: The Role Of Community Development Within Social Workmentioning
confidence: 99%
See 1 more Smart Citation